2022
DOI: 10.1177/10398562221077895
|View full text |Cite
|
Sign up to set email alerts
|

How peer review groups support learning and wellbeing in psychiatrists

Abstract: Objective To explore the self-reported value of Peer Review Groups (PRGs) by Australian psychiatrists, focussing on learning and wellbeing. Methods A cross-sectional mixed-methods online survey of psychiatrists registered with the NSW Branch Royal Australian and New Zealand College of Psychiatrists (RANZCP) who had attended a PRG in the previous 12 months. Results Respondents described PRG participation as supportive to their learning and to their professional wellbeing by sharing professional experiences, emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“… 15 (11) Psychiatrists’ therapeutic equipoise can be restored through the learning and well-being function of peer review groups. 16 Enthusiasm about a novel treatment may be balanced by careful scrutiny of the accumulated evidence-base. Positive and negative countertransference reactions may be reflected upon, and patient-focused care re-established.…”
Section: Principles Of Psychiatric Therapeutic Equipoisementioning
confidence: 99%
“… 15 (11) Psychiatrists’ therapeutic equipoise can be restored through the learning and well-being function of peer review groups. 16 Enthusiasm about a novel treatment may be balanced by careful scrutiny of the accumulated evidence-base. Positive and negative countertransference reactions may be reflected upon, and patient-focused care re-established.…”
Section: Principles Of Psychiatric Therapeutic Equipoisementioning
confidence: 99%
“…Another possible strategy is the use of self-directed peer review groups, which psychiatrists report as supporting learning and wellbeing by providing a collegial space for processing emotional aspects of their practice. 13 An electronic hub (eg, The Essential Network 14 ) containing health information, screening tools, evidence-based treatment guidelines, and selfadministered structured psychological treatments may address time and confidentiality barriers for doctors.…”
Section: Reducing Barriers To Help Seekingmentioning
confidence: 99%
“…Enhancing the capacity of doctor‐peer support groups such as Hand‐n‐Hand peer support network 12 would ensure better access to regular peer support within a structure that maintains a necessarily safe space. Another possible strategy is the use of self‐directed peer review groups, which psychiatrists report as supporting learning and wellbeing by providing a collegial space for processing emotional aspects of their practice 13 …”
Section: Reducing Barriers To Help Seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…In doctors, it has been shown that the need for relatedness has the largest unique contribution to professional well-being, as manifested by exhaustion, satisfaction with professional life and work-related engagement. 7 Moreover, remedies such as mentoring, Peer Review 8 and Peer Support 9 groups have demonstrated benefits for supporting professional practice and countering isolation. Rather than despair, working on these wicked problems together can perhaps, lead to a sense of hope.…”
mentioning
confidence: 99%